Ruído ocupacional das atividades mecanizada e semimecanizada da colheita do café - SILVA, José Antonio Ramos da (2018)
The use of mechanized equipment in the production of coffee is a tool that optimizes processes, improves production and consequently reduces costs. However, the noise generated by the machines can expose workers to sound pressure levels can be harmful to their health, and can lead to these workers to emotional, psychological and social problems. Among them, hearing loss is one of the main problems that can be aggravated by the time and the level of exposure of this worker. In the present study, the objective was to quantify the level of occupational noise generated by the most used equipment in the mechanized and semi-mechanized harvesting of coffee, and in Article 1, the objective was to determine the occupational noise level in the mechanized and semi-mechanized harvesting activities of the fruits of coffee and compares them with the limits of tolerance of the current legislation. And in Article 2, to evaluate the spatial variability of the noise generated by an automotive coffee harvester with the use of the geostatistical analysis. For the data collection, was used: automotive coffee harvester, a blower, two different pickers, an auxiliary worker that remained in the back of the collector and portable mechanical stripper. The data were collected in the auditory zone of the workers by dosimeter and decibelimeter duly calibrated electromechanically and configured according to the norms of NR 15 and NHO 01. The results showed that in the comparison of the noise levels between the semi-mechanized and mechanized harvest were above the permitted by the current legislation, which is 85 dB (A) for an 8-hour day, with the lowest and highest occupational noise level found was 89.05 dB (A) and 100.66 dB (A) for the auxiliary of the collector and blower, respectively, and that semi-mechanized harvesting activity is 4.07% noisier in comparison to the automotive harvester. As for the spatial variability of the noise generated by the automotive harvester, a strong degree of spatial dependence was obtained between the points sampled with a range of 9.5 m, which can be seen by the maps of isolines, and those who suffer most from the levels of noise emitted, by the equipment is the operator, but the workers that are within a distance of up to 5.5m from the generating source are also being affected by noise levels above those allowed. Therefore, equipment operators and workers who are close to the coffee machine should use personal protective equipment.